1998
DOI: 10.1044/1058-0360.0703.39
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Recruitment and Retention of Historically Underrepresented Minority Students in Higher Education

Abstract: There is a need for more bilingual and/or minority speech-language pathologists to serve an increasingly diverse population. To recruit and retain minority students, faculty in university training programs should increase their awareness of minority students’ needs and expectations. This paper reviews the literature pertaining to the factors relating to minority students’ success in higher education and reports the results of a survey designed to assess students’ perceptions of factors related to academic succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Mismatches in client-clinician language backgrounds are occurring with increasing frequency. First, the majority of SLPs in the U.S. are native speakers of English (Kritikos, 2003; Saenz, Wyatt, & Reinard, 1998), resulting in an inadequate number of SLPs to serve the growing number of multilingual clients. In 2009, for example, less than 6% of ASHA members identified as multilingual or bilingual (ASHA, 2010a).…”
mentioning
confidence: 99%
“…Mismatches in client-clinician language backgrounds are occurring with increasing frequency. First, the majority of SLPs in the U.S. are native speakers of English (Kritikos, 2003; Saenz, Wyatt, & Reinard, 1998), resulting in an inadequate number of SLPs to serve the growing number of multilingual clients. In 2009, for example, less than 6% of ASHA members identified as multilingual or bilingual (ASHA, 2010a).…”
mentioning
confidence: 99%
“…If students perceive limited support to participating in graduate CSD programs, students may not be successful despite interest or ability. In particular, social supports are critical for success of students from diverse groups (Saenz, Wyatt, & Reinard, 1998). Solberg and Viliarreal (1997) reported that Hispanic college students who perceived strong social support had less stress and higher selfefficacy.…”
Section: Barrier To Csd Professions: Social Supportmentioning
confidence: 99%
“…It should also be noted that ASHA’s (1998) position statement and technical report focused on SLPs with accents in English. As most SLPs in the United States are native speakers of English (ASHA, 2004; Kritikos, 2003; Saenz, Wyatt, & Reinard, 1998), a more frequent scenario than SLPs with accents in English is native speakers of American English providing SLP services in Spanish. With L2s learned at an average age of 12 years old in the United States (Pufahl, Rhodes, & Christian, 2001), beyond many individuals’ “critical” or “sensitive” period in phonological development, it is likely that a majority of the native speakers of English working bilingually in the United States have American English accents in Spanish.…”
Section: Implications For Modifying Accent or Increasing Intelligibilitymentioning
confidence: 99%